Non-uniqueness for the Euler equations: The effect of the boundary - Bardos, C.; Szekelyhidi, L.; Wiedemann, Emil (Russian Mathematical Surveys, 2014)
Rotational initial data is considered for the two-dimensional incompressible Euler equations on an annulus. With use of the convex integration framework it is shown that there exist infinitely many admissible weak solutions (that is, with non-increasing energy) for such initial data. As a consequence, on bounded domains there exist admissible weak solutions which are not dissipative in the sense of Lions, as opposed to the case without physical boundaries. Moreover, it is shown that admissible solutions are dissipative if they are Hölder continuous near the boundary of the domain. © 2014 Russian Academy of Sciences (DoM), London Mathematical Society, Turpion Ltd.
CRIS-Team Scopus Importer:2023-01-17
Keywords: Boundary effects; Convex integration; Dissipative solutions; Euler equations; Inviscid limit; Non-uniqueness; Rotational flows; Wild solutions